Study of degenerative (non-lytic) spondylolisthesis grade 1 and 2 in axial MRI images - Surana, Amit; Gadkari, Alok; Gore, Satishchandra (International Journal of Research in Orthopaedics, 2024)
Background: The traditional imaging assessment of lumbar spondylolisthesis is in sagittal images noting movement of upper body over the lower body. It omits change at the facet. Methods: The present observational, study included 35 patients with degenerative lumbar spondylolisthesis(non-lytic). Radiological analysis of all MRI images was done by 4 independent spinal surgeons and 2 radiologists. The study focused on the axial MRI images and changed relation between the superior articular process and inferior articular process and relation between inferior articular process and canal with thecal sac (traversing root). Results: Majority of DS had sagittal oriented facets (71.43%). In 7 cases at the L3/4 and in 19 cases at L4/5 level both facet joints had sagittal orientation with forward (ventral) movement of IAP. The IAP was found to be encroaching or in close proximity of traversing root. In 1 patient at L3/4 and 6 patients at L4/5 joint was sagittal unilaterally, may be causing compression of the neural elements unilaterally, while on coronal side the IAP and SAP had a normal alignment and not causing neural encroachment Conclusions: We need to concentrate on relation of IAP vs SAP at facet as seen in axial images of facet.